Resiko Penyakit Tidak Menular Pada Masyarakat Usia Produktif (15-64 Tahun) Di Kota Banjarmasin di Era Society 5.0 - Oktovin; Unja, Ermeisi Er; Maratning, Anastasia; Rachman, Aulia (Journal of Nursing Invention, 2024)
Background: In the current Era of Society 5.0, the use of technology by the majority of society is actually increasing. It is hoped that the use of technological development can provide convenience for users, both in obtaining information, communicating, getting goods easily and even helping with working. It’s just that convenience offered will have a negative impact on society. Among other things, changes in activity patterns and eating patterns of people of productive age. So that the increase in body weight above normal or obesity and the risk of non-communicable diseases increases. Objective: This research aims to describe physical activity patterns, daily food consumption patterns and body weight status which are considered to contribute to the triggering of non-communicable diseases in people of productive age in Banjarmasin City, South Borneo, Indonesia Method: This research is quantitative descriptive research. The sample for this research consisted of 274 people spread across 5 areas in Banjarmasin City. The sample for this research was selected using a non-probability sampling technique, namely purposive sampling. This research instrument uses a questionnaire, namely the Baecke Questionnaire for physical activity, anthropometric data collection including height and weight, and the Food Frequency Questionnaire (FFQ) for eating patterns. Data analysis using SPSS version 16 with descriptive analysis. Result: The findings of this research show that the majority of productive age people's activity patterns in Banjarmasin City are in the low category (97.4%), with poor eating patterns (87.2%) and the majority's weight status in the normal category (51.9%). Conclusion: The physical activity of people of productive age in Banjarmasin City tends to be in the low category and their eating patterns are in the poor category. This finding can illustrate that the majority of people in Banjarmasin City are at risk of various non-communicable diseases.